English Teacher Strategies in Motivating Low-Achiever Students - Adinda Wahyu Budiyanti (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Teacher motivation strategies are defined as methods and techniques to generate and maintain student motivation (Sugita & Takeuchi, 2010). Dornyei (2001) defines motivational strategies as a technique that offers human behavior and is related to certain goals. Teachers can play a role in increasing the level of motivation of their students so that they can improve their learning achievement. Bearing this in mind, the question of what teacher can do to increase student motivation has great significance. This brings us to the most central issue in this research: teacher motivation strategies for low-achieving students. The focus of this study is to find out how the English teacher uses strategies in motivating low-achiever students. This research was conducted in a senior high school in Jember using a case study research design. This research design was chosen because the aim is to understand individuals intensively, which is useful for achieving better adjustment, and also to understand all matters related to what was studied in this research. There was one English teacher who participated in this study, and data was collected through classroom observation and used field notes. The researcher observed how teacher and students perform during teaching and learning activities from the beginning of the learning session, the core activities, to the closing. To analyze the data, I used content analysis; the organizing stage includes familiarizing, open coding, creating categories, and interpretation. In transcribing videos, the English teacher revealed several key codes and strategies in motivating low-achiever students. The analysis focused on recurring patterns and teacher strategies. The next step was to classify the coded texts that belonged to the same category, and the coding process was based on the evolving data. Then, the last step was developing an explanation that best represented the code generated and discussed in order to draw a conclusion.
Reaploud Repository February_agus
Keywords: English teacher; Motivating; Low Achievers